Dynamic modeling of absorption/desorption closed-loop including periphery - Bothe, Mike; Hami Dindar, Iman; Lutters, Nicole; Kenig, Eugeny Y. (Computers and Chemical Engineering)

Institutionen der Medienpädagogik. Erwachsenen- und Weiterbildung - Meister, Dorothee M.; Dehmel, Lukas (Handbuch Medienpädagogik.)

Joining of multi-material structures using a versatile self-piercing riveting process - Kappe, Fabian; Wituschek, Simon; Bobbert, Mathias; Lechner, Michael; Meschut, Gerson (Production Engineering)
Due to the increasing use of multi-material constructions and the resulting material incompatibilities, mechanical joining technologies are gaining in importance. The reasons for this are the variety of joining possibilities as well as high load-bearing capacities. However, the currently rigid tooling systems cannot react to changing boundary conditions, such as changed sheet thicknesses or strength. For this reason, a large number of specialised joining processes have been developed to expand the range of applications. Using a versatile self-piercing riveting process, multi-material structures are joined in this paper. In this process, a modified tool actuator technology is combined with multi-range capable auxiliary joining parts. The multi-range capability of the rivets is achieved by forming the rivet head onto the respective thickness of the joining part combination without creating a tooling set-up effort. The joints are investigated both experimentally on the basis of joint formation and load-bearing capacity tests as well as by means of numerical simulation. It turned out that all the joints examined could be manufactured according to the defined standards. The load-bearing capacities of the joints are comparable to those of conventionally joined joints. In some cases the joint fails prematurely, which is why lower energy absorptions are obtained. However, the maximum forces achieved are higher than those of conventional joints. Especially in the case of high-strength materials arranged on the die side, the interlock formation is low. In addition, the use of die-sided sheets requires a large deformation of the rivet head protrusion, which leads to an increase in stress and, as a result, to damage if the rivet head. However, a negative influence on the joint load-bearing capacity could be excluded.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

Provision of cross-domain knowledge in mechanical joining using ontologies - Zirngibl, Christoph; Kügler, Patricia; Popp, Julian; Bielak, Christian Roman; Bobbert, Mathias; Drummer, Dietmar; Meschut, Gerson; Wartzack, Sandro; Schleich, Benjamin (Production Engineering)
Since the application of mechanical joining methods, such as clinching or riveting, offers a robust solution for the generation of advanced multi-material connections, the use in the field of lightweight designs (e.g. automotive industry) is steadily increasing. Therefore, not only the design of an individual joint is required but also the dimensioning of the entire joining connection is crucial. However, in comparison to thermal joining techniques, such as spot welding, the evaluation of the joints’ resistance against defined requirements (e.g. types of load, minimal amount of load cycles) mainly relies on the consideration of expert knowledge, a few design principles and a small amount of experimental data. Since this generally implies the involvement of several domains, such as the material characterization or the part design, a tremendous amount of data and knowledge is separately generated for a certain dimensioning process. Nevertheless, the lack of formalization and standardization in representing the gained knowledge leads to a difficult and inconsistent reuse, sharing or searching of already existing information. Thus, this contribution presents a specific ontology for the provision of cross-domain knowledge about mechanical joining processes and highlights two potential use cases of this ontology in the design of clinched and pin joints.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

Investigation of the friction conditions of self-pierce rivets by means of a compression-torsion tribometer - Rossel, Moritz Sebastian; Meschut, Gerson (Production Engineering)
Lightweight design is an effective lever for achieving fuel consumption and emission-oriented goals. Therefore micro-alloyed steels and high-strength aluminium materials are included in the multi-material mix of the car body. In this context self-pierce riveting has become established for joining in body-in-white production. For the dimensioning of the joint, numerical simulation is increasingly being used. In order to make reliable predictions about joint quality, knowledge of the friction in the joining process is necessary and needs to be identified experimentally. In previous investigations, the process parameters in the friction test were not comparable to the joining process. Therefore, a new friction test method is presented in this paper, where the process conditions are comparable between joining and friction testing especially regarding the interface pressure. The local joining process parameters between rivet and sheet are derived numerically. In the framework of the investigations, the influences of the local joining process parameters, like interface pressure, relative velocity and temperature, on the friction are investigated and mapped close to the joining process. Additionally a comparison of different rivet coatings is carried out. The rivet contact to the sheet metal HX340LAD as well with aluminium EN AW-5182 is taken into account.

Numerical Investigation of the Influence of a Movable Die Base on Joint Formation in Semi-tubular Self-piercing Riveting - Kappe, Fabian; Wituschek, Simon; de Pascalis, Vincenzo; Bobbert, Mathias; Lechner, Michael; Meschut, Gerson (Materials Design and Applications IV)
Due to economic and ecological requirements and the associated trend towards lightweight construction, mechanical joining technologies like self-piercing riveting are gaining in importance. In addition, the increase in lightweight multi-material joints has led to the development of many different mechanical joining technologies which can only be applied to join a small number of material combinations. This leads to low process efficiency, and in the case of self-piercing riveting, to a large number of required tool changes. Another approach focuses on reacting to changing boundary conditions as well as the creation of customised joints by using adaptive tools, versatile auxiliary joining parts or modified process kinematics. Therefore, this study investigates the influence of increased die-sided kinematics on joint formation in self-piercing riveting process. The aim is to achieve an improvement of the joint properties by superimposing the punch feed. Furthermore, it is intended to reduce required tool changes due to the improved joint design. The investigations were carried out by means of a 2D-axisymmetric numerical simulation model using the LS-Dyna simulation software. After the validation of the process model, the die was extended to include driven die elements. Using the model, different kinematics as well as their effects on the joint formation and the internal stress concentration could be analysed. In principle, the increased actuator technology enabled an increase of the interlock formation for both pure aluminium and multi-material joints consisting of steel and aluminium. However, the resulting process forces were higher during the process phases of punching and spreading.

Determining the influence of different process parameters on the versatile self-piercing riveting process using numerical methods - Kappe, Fabian; Zirngibl, Christoph; Schleich, Benjamin; Bobbert, Mathias; Wartzack, Sandro; Meschut, Gerson (Journal of Manufacturing Processes)
Keywords: Industrial and Manufacturing Engineering; Management Science and Operations Research; Strategy and Management

Increasing flexibility of self-piercing riveting by reducing tool–geometry combinations using cluster analysis in the application of multi-material design - Kappe, Fabian; Schadow, Luca; Bobbert, Mathias; Meschut, Gerson (Proceedings of the Institution of Mechanical Engineers Part L Journal of Materials Design and Applications)

Determining the properties of multi‑range semi‑tubular self‑piercing riveted joints - Kappe, Fabian; Wituschek, Simon; Bobbert, Mathias; Meschut, Gerson (Production Engineering)

Literature study on the potential of Artificial Intelligence in Scenario-Technique - Gräßler, Iris; Tusek, Alena Marie; Thiele, Henrik; Preuß, Daniel; Grewe, Benedikt; Hieb, Michael (XXXIII ISPIM Innovation Conference Proceedings)

NTFA-enabled goal-oriented adaptive space–time finite elements for micro-heterogeneous elastoplasticity problems - Ju, X.; Mahnken, Rolf; Xu, Y.; Liang, L. (Computer Methods in Applied Mechanics and Engineering)
Keywords: Computer Science Applications; General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; Computational Mechanics

A polymorphic uncertainty model for the curing process of transversely fiber-reinforced plastics - Penner, Eduard; Caylak, Ismail; Mahnken, Rolf (Mathematics and Mechanics of Complex Systems)
Keywords: Computational Mathematics; Numerical Analysis; Civil and Structural Engineering

New low order Runge–Kutta schemes for asymptotically exact global error estimation of embedded methods without order reduction - Mahnken, Rolf (Computer Methods in Applied Mechanics and Engineering)
Keywords: Computer Science Applications; General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; Computational Mechanics

Efficient Extraction of Technical Requirements Applying Data Augmentation - Gräßler, Iris; Preuß, Daniel; Brandt, Lukas; Mohr, Michael (Proceedings of 8th IEEE International Symposium on Systems Engineering 2022)

Gestaltung einer Forschungsinfrastruktur für die Anwendung digitaler Werkzeuge in Cyber-Physischen Produktionssystemen - Gräßler, Iris; Hieb, Michael; Roesmann, Daniel (Automation 2022)

Manufacture of Defined Residual Stress Distributions in the Friction-Spinning Process: Driven Tool and Subsequent Flow-Forming - Dahms, Frederik; Homberg, Werner (Key Engineering Materials)
Friction-spinning as an innovative incremental forming process enables large degrees of deformation in the field of tube and sheet metal forming due to a self-induced heat generation in the forming zone. This paper presents a new tool and process design with a driven tool for the targeted adjustment of residual stress distributions in the friction-spinning process. Locally adapted residual stress depth distributions are intended to improve the functionality of the friction-spinning workpieces, e.g. by delaying failure or triggering it in a defined way. The new process designs with the driven tool and a subsequent flow-forming operation are investigated regarding the influence on the residual stress depth distributions compared to those of standard friction-spinning process. Residual stress depth distributions are measured with the incremental hole-drilling method. The workpieces (tubular part with a flange) are manufactured using heat-treatable 3.3206 (EN-AW 6060 T6) tubular profiles. It is shown that the residual stress depth distributions change significantly due to the new process designs, which offers new potentials for the targeted adjustment of residual stresses that serve to improve the workpiece properties.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Manufacture of Defined Residual Stress Distributions in the Friction-Spinning Process: Investigations and Run-to-Run Predictive Control - Dahms, Frederik; Homberg, Werner (Metals)
Friction-spinning as an innovative incremental forming process enables high degrees of deformation in the field of tube and sheet metal forming due to self-induced heat generation in the forming area. The complex thermomechanical conditions generate non-uniform residual stress distributions. In order to specifically adjust these residual stress distributions, the influence of different process parameters on residual stress distributions in flanges formed by the friction-spinning of tubes is investigated using the design of experiments (DoE) method. The feed rate with an effect of −156 MPa/mm is the dominating control parameter for residual stress depth distribution in steel flange forming, whereas the rotation speed of the workpiece with an effect of 18 MPa/mm dominates the gradient of residual stress generation in the aluminium flange-forming process. A run-to-run predictive control system for the specific adjustment of residual stress distributions is proposed and validated. The predictive model provides an initial solution in the form of a parameter set, and the controlled feedback iteratively approaches the target value with new parameter sets recalculated on the basis of the deviation of the previous run. Residual stress measurements are carried out using the hole-drilling method and X-ray diffraction by the cosα-method.
Keywords: General Materials Science; Metals and Alloys

Fracture mechanical evaluation of the material HCT590X - Schramm, Britta; Weiß, Deborah (Materials Testing)
For a reliable, strength-compliant and fracture-resistant design of components and technical structures and for the prevention of damage cases, both the criteria of strength calculation and fracture mechanics are essential. In contrast to strength calculation the fracture mechanics assumes the existence of cracks which might further propagate due to the operational load. First, the present paper illustrates the general procedure of a fracture mechanical evaluation of fatigue cracks in order to assess practical damage cases. Fracture mechanical fundamentals which are essential for the calculation of the stress intensity factors K I and the experimental determination of fracture mechanical material parameters (e.g. threshold Δ K I,th against fatigue crack growth, crack growth rate curve) are explained in detail. The subsequent fracture mechanical evaluation on the basis of the local stress situation at the crack tip and the fracture mechanical material data is executed for different materials and selected crack problems. Hereby, the main focus is on the material HCT590X as it is the essential material being investigated by TRR285.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Impact of aging on the energy efficiency of household refrigerating appliances - Paul, Andreas; Baumhögger, Elmar; Elsner, Andreas; Reineke, Michael; Hueppe, Christian; Stamminger, Rainer; Hoelscher, Heike; Wagner, Hendrik; Gries, Ulrich; Becker, Wolfgang; Vrabec, Jadran (Applied Thermal Engineering)
The parameters required to calculate the energy efficiency of household refrigerating appliances (i.e. refrigerators, freezers and their combinations) are determined by standard measurements. According to regulations, these measurements are carried out when the appliances are new. It is known from previous studies that various technical aging mechanisms can increase electrical energy consumption by up to 36 % over a product lifespan of 18 years. In order to determine the time dependence of the energy consumption of household refrigerating appliances, repeated measurements are carried out in this work. Eleven new appliances are examined under standard measurement conditions. After just two years of operation, an additional energy consumption of up to 11 % is determined. Furthermore, 21 older appliances that had previously been measured in new condition are tested again after up to 21 years of operation. For these older appliances, an average increase of energy consumption of 28 % is found. For individual appliances, the maximum increase is 36 %. An aging model is developed on the basis of these measurement results, which may help to predict the aging-related increase of energy consumption of household refrigerating appliances. This model shows an average increase in energy consumption of 27 % for an appliance age of 16 years. Supplemental performance tests of eight compressors do not show any significant aging effects related to these devices after two years of operation. Furthermore, measurements of the thermal conductivity of aged polyurethane foam test samples are carried out and an increase of its thermal conductivity of 26 % over a period of about three years is determined.
Keywords: Industrial and Manufacturing Engineering; Energy Engineering and Power Technology

Apparatus for the measurement of the thermodynamic speed of sound of diethylene glycol and triethylene glycol - Javed, Muhammad Ali; Vater, Sebastian; Baumhögger, Elmar; Windmann, Thorsten; Vrabec, Jadran (The Journal of Chemical Thermodynamics)
Keywords: Physical and Theoretical Chemistry; General Materials Science; Atomic and Molecular Physics; and Optics